The interface tension of the three-dimensional Ising model in the scaling region - Hasenbusch, Martin; Pinn, Klaus (Physica. A, Statistical mechanics and its applications, 1997)
Using the Monte Carlo method, we determine the free energy of the interface of the 3D Ising model in the scaling region. By integrating the interface energies over the inverse temperature β, we obtain estimates for the free energies of interfaces with cross sections up to 96 × 96, and for a range 0.223⩽β⩽0.23. Our data yield a precise estimation of the interface tensions σ. We determine the amplitude σ0 in the critical law σ ∼ σ0tμ and estimate the combination σξ2 which yields the universal constant R_ in the critical limit.